Endoscopic stenting for palliation of intra-abdominal gastrointestinal malignant obstruction: predictive factors for clinical success. Issue 9 (September 2018) - Pais-Cunha, Inês; Castro, Rui; Libânio, Diogo; Pita, Inês; Bastos, Rui P.; Silva, Rui; Dinis-Ribeiro, Mario; Pimentel-Nunes, Pedro
Abstract : Background: Endoscopic stenting proved to be a safe alternative to surgery for malignant intra-abdominal gastrointestinal obstruction. Although high technical success rates have been reported, some patients do not experience relief in symptoms. Aim: This study aimed to analyse the factors predicting the effectiveness of stent placement in patients with gastrointestinal obstruction. Patients and methods: A retrospective study was carried out including 160 patients who underwent palliative stenting for intra-abdominal obstruction in a tertiary centre from December 2012 to July 2017. Technical and clinical success, stent dysfunction and adverse events were analysed. Results: The rate of technical success was 98%. The rate of early clinical success was 69 and 81% in upper and lower gastrointestinal obstructions, respectively ( P =0.107). In the upper tract, obstruction caused by carcinomatosis was the only independent factor predicting early and late clinical failure [odds ratio (OR): 9.7, 95% confidence interval (CI): 2.5–38.4, P =0.001 and OR: 7.6, 95% CI: 1.8–31.9, P =0.006, respectively]. In the colon, Eastern Cooperative Oncology Group score of at least 3 was an independent factor for early clinical failure (OR: 29.8, 95% CI: 1.9–464.9, P =0.002) and obstruction caused by carcinomatosis was an independent factor for late clinical failure (OR: 14.4, 95% CI: 1.7–119.6, P =0.013). Perforation occurred in 4 patients (2.5%) and stent dysfunction occurred in 15% of patients (4% stent migration; 9% restenosis). Carcinomatosis was a risk factor for perforation ( P =0.039) and migration was higher with shorter 6 cm stents ( P =0.044). Conclusion: Stents are effective and safe for palliation of intra-abdominal obstruction. Carcinomatosis predicts an unfavourable clinical outcome. Palliative stenting as an option should be weighed carefully in these patients.